In the Shackles of Instability: Challenges of Operation Barkhane in the G5 Sahel Countries - Godó, Judit (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Suffering from a multidimensional crisis, the Sahel has morphed into the new center of terror. In the past few years, it has become one of the most hazardous places in the world, which has negatively transformed the fragile states of the Western-African region. Emerging as a novel security policy challenge, the G5 Sahel countries – namely Burkina Faso, Chad, Mali, Mauritania, and Niger – have found themselves stuck in a quagmire of different deep-rooted human security issues, which have placed their populations in a vicious circle of closely intertwined problems. Various influences threaten not just the security of residents and foreign actors but also the security of neighboring states. Different regional and international actors are trying to solve this complex crisis with varying levels of success. In this environment, in the shackles of instability, the presence of jihadist terrorist organizations and the operations of different rebel armed forces independent from governments pose a growing threat by making Sahelian life a living hell. This paper aims to discuss the challenges and effectiveness of Operation Barkhane, the terminating counter-terrorism operation led by the French, which has started its strategical transformation by merging into the European initiative known as the Takuba Task Force. Under President Emmanuel Macron, France remains the most important actor in the international community. In close alliance and cooperation with the African leaders and military forces of the five countries involved, they have been fighting terrorism within the confines of Operation Barkhane since 2014. Until recently 5,100 French soldiers have been deployed. They risk their lives every day in an incredibly hostile and constantly changing field where either they or the jihadists are under fire. Even though this operation has become an essential part of providing security in these countries, French participation remains controversial: despite their willingness to help, heavily armed French soldiers are not the most popular throughout the region. The importance of the topic speaks for itself because the transformation of the operation and the withdrawal of half of the French troops may have a drastic impact on the future of the Sahel.